0071 A Medullary Circuit Controlling REM Sleep. (27th May 2020) - Schott, A; Baik, J; Chung, S; Weber, F
Abstract: Introduction: Rapid eye movement (REM) sleep is a distinct brain state known for its association with vivid dreaming in humans, though it is also crucial for other mental processes such as memory consolidation and emotion regulation. REM sleep is punctuated by phasic neurophysiological events known as pontine (P)-waves, which are thought to contribute to the cognitive functions of REM sleep. However, little is known about the neural circuits regulating these P-waves, or those responsible for initiating REM sleep itself. Here, we show that a yet unstudied population of medullary neurons expressing corticotropin-releasing-hormone (CRH) are important for controlling both the induction of REM sleep and its phasic events. Methods: To measure the endogenous activity of CRH+ neurons in the dorsomedial medulla (dmM), we injected the calcium indicator GCaMP6 in the dmM of CRH-Cre mice. To optogenetically manipulate dmM CRH+ neuron activity, we delivered either an excitatory (ChR2) or inhibitory (iC++) opsin to the dmM of CRH-Cre mice. To record P-waves, we implanted microelectrodes to record local field potentials in the subcoeruleus region of the pons. Results: Fiber photometry recordings showed that dmM CRH+ neurons are selectively active during REM sleep, and optogenetic stimulation and inhibition of this population is sufficient to promote and reduce REM sleep, respectively. Additionally, dmM CRH+ neuron activity is correlated with P-waves in the pons, and optogenetic activation of dmM CRH+ cells reliably triggers P-waves during REM sleep. Finally, histological examination of fluorescently labeled dmM CRH+ axons revealed strong projections to several pontine areas involved in P-wave generation as well as modulation of the theta rhythm during REM sleep. Conclusion: Our results suggest that dmM CRH+ neurons are involved in controlling REM sleep initiation as well as phasic events within REM sleep. These neurons thus constitute an important component of the brainstem circuitry regulating REM sleep. Support: National Institutes of Health (R01 HL149133)